Zbtb7b defines a compensatory mechanism in MASLD‐related HCC progression by suppressing H19‐mediated hepatic lipid deposition - Yinglin Han; Kaimin Wu; Xin Peng; Yinkun Fu; Wenyan Li; Jing Ma; He Jiang; Xu‐Yun Zhao (Physiological Reports)
Abstract Hepatocellular carcinoma (HCC) is a widely prevalent type of primary liver cancer. However, strategies for pretumor intervention are still limited. In this study, a liver‐specific Zbtb7b knockout mouse model was used to evaluate the role of Zbtb7b in metabolic dysfunction‐associated steatotic liver disease (MASLD)‐related HCC development. We revealed that Zbtb7b was compensatively increased and restricted lipid deposition in the liver during MASLD progression, which protects against MASLD‐related HCC initiation. Mechanistically, Zbtb7b suppresses the expression of the long noncoding RNA H19 to attenuate hepatic de novo lipogenesis and increase fatty acid oxidation, thereby preventing lipid accumulation in hepatocytes. As a result, the proliferation and migration abilities of HCC cells are reduced. Overall, we demonstrated that Zbtb7b serves as a tumor suppressor at an early stage of HCC, thus providing a promising target for the treatment of HCC at a premalignant stage.